ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MENJADI NASABAH BADAN KREDIT DESA (BKD) BOGARES KIDUL - Ari Susantiaji; Nurhadi Kamaluddin (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
This study aims to determine the effect of location, service, product and interest rates on the decision to become a customer of BKD Kidares. The data used in this study is quantitative data. The analytical method used in this research is quantitative descriptive method. The variables in this study are Location (X1), Services (X2), Products (X3) and Interest Rates (X4). Based on the SPSS (Statistical for Package Social Sciences) test, the results of hypothesis testing using multiple linear regression equations, the four variables have a positive effect on the decision to become a customer of BKD Kidares, the location variable has a positive effect with a coefficient value of 0.438, the service variable has a positive effect on the coefficient value is 0.068, the product variable has a positive effect with a coefficient value of 0.360, and the interest rate variable has a positive effect with a coefficient value of 0.156.